Immediate effect of Mulligan taping on joint position sense and muscle strength in amateur wrestlers - Naserpour, H.; Letafatkar, A.; Habibi, H. (International Journal of Wrestling Science, 2020)
The knee is one of the most frequent sites of injuries in wrestling. Taping techniques are commonly used in other to reduce the pain and incidence of knee injuries in physical activities. This study aimed to investigate the immediate effect of mulligan taping on joint position sense and muscle strength in amateur wrestlers. Twelve Amateur freestyle wrestlers (Mean age 23±3 years old, weight 68±12 kg and height 176±12 cm) volunteered to participate as subjects in this study. The reproduce angle and dynamometer speed test was considered 60° and 5 O/sec respectively and peak torque of concentric and eccentric of quadriceps muscle groups tested at 90 O/sec by using an isokinetic dynamometer (Biodex Model, System 3, Made in USA) Before and after Mulligan taping. Data were analyzed by using Origin Pro (2019) and SPSS software (version 25). The Shapiro-Wilk test was used to check the normality distribution of the data, and a paired t-test was adopted to compare the results before and after taping at a significant level (P=0.05). The statistics showed significant differences between active (p=0.001) and passive (p=0.002) Repositioning errors before and after taping. Also, there were significant differences between the Maximum concentric (p=0.003) and eccentric (p=0.002) torque of the quadriceps muscle group before and after taping. It seems that Mulligan taping could improve the knee proprioception and increase maximum concentric and eccentric extensor torques. It is highly recommended that to provide more comprehensive information by conducting more sample research size about the use of taping (Mulligan method) during the treatment of knee injuries in wrestling.